Comprehensive evaluation of modern combine harvester performance in Southern Russia - M. E. Chaplygin; E. V. Zhalnin (Сельскохозяйственные машины и технологии, 2024)
Given the diverse range of machines used on farms (including different brands, models, and manufacturers, etc.), the absence of regulatory guidelines often results in violations of optimality and harmony within the equipment fleet. This, in turn, leads to increased costs of finished products. (Research purpose) This study aims to generalize the results from testing grain harvesters in the southern regions of Russia and to provide a comprehensive assessment of their operational efficiency. (Materials and methods) Tests were conducted on economic entities in Southern Russia using a unified, standardized program and methodology according to GOST 28301-2015, GOST 24055-2016, and STO AIST 8.22-2010. A comprehensive assessment of combine harvesters was conducted evaluating operational and technological performance, energy consumption, and economic criteria. (Results and discussion) A technical analysis of 12 models of foreign and domestically-produced combines has revealed key characteristics that influence their productivity and operational quality. These combines exhibit a throughput capacity ranging from 6.7 kilograms per second (Nova S 340) to 13.8 kilograms per second (John Deere S690), and their engine powers vary between 180 and 530 horsepower. The specific engine power per unit of throughput also varies, ranging from 24.0 to 38.4 horsepower. Axial rotary combines are noted for their high productivity and minimal grain loss. They offer benefits such as reduced grain crushing and low levels of impurity in bunker grain. The average fuel consumption of these combines is recorded at 11.2 kilograms per hectare. (Conclusions) In terms of grain loss, grain crushing, purity, and fuel consumption, domestic combines are comparable to their foreign counterparts, and meet standard agrotechnical requirements. It is recommended that domestic designers study the cleaning mechanisms of the Laverda combine, which ensure minimizing the impurity levels in bunker grain. The cost of the combines analysed does not correlate proportionally with their increased productivity, leading to a signifi cant (up to 40%) rise in the cost of harvesting operations. The Don-1500B combine harvester shows superior economic performance, including direct and capital costs, compared to its counterparts. Therefore, discontinuing its production would be premature.